Peran Expert Prescriber Dan Problem Solving Process Facilitator Humas Pemprov Kalsel Dalam Melayani Informasi Publik - Belinda Devi Larasati Siswanto (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2016)
This study focuses PR government that has a function as an expert Presciber and Problem Solving Process Facilitator in strengthening the Government Relations function itself. This research was conducted with a qualitative approach with descriptive case study method, this research was conducted at the office of the Public Relations Bureau of the Regional Secretariat of South Kalimantan Province. Last data collection techniques dept interviews using a semi-structured interview, Determination Key Person who used informants in this study taking into-hatikan level of concordance (relevance) between the position / positions and Keter-informant involvement in the process of public information disclosure. The results showed the PR Bureau does not fulfill the role as an expert prescriber in the activities he does. Meanwhile, the role of problem solving process facilitator nothing visible in the PR Bureau, this is because the PR Bureau has not run verification and inventory information to be discussed by senior management. Suggestion of this study Public Relations Bureau of South Kalimantan province can utilize the human resources that already exist to have the ability to perform tasks as a public relations major government and PPID in South Kalimantan province, given the uneven coordination between the Bureau of Public Relations section. The next PR Bureau should be possible to plan a program of activities and their sustainable strategies for the acceleration of public disclosure. Keywords: Public Relations, Government, Expert prescriber, Problem Solving Facilitator precess ABSTRAK Penelitian ini menitikberatkan Humas pemerintah yang memiliki fungsi sebagai expert Presciber dan Problem Solving Process Facilitator dalam menguatkan fungsi Humas Pemerintah itu sendiri. Penelitian ini dilakukan dengan pendekatan kualitatif dengan metode studi kasus deskriptif, Penelitian ini dilakukan di kantor Biro Humas Sekretariat Daerah Provinsi Kalimantan Selatan. Teknik pengumpulan data terakhir yakni wawancara mendalam dengan menggunakan wawancara semi terstruktur, Penentuan Key Person yang dijadikan narasumber dalam penelitian ini dengan memper-hatikan tingkat kesesuaian (relevansi) antara kedudukan/ jabatan dan keter-libatan informan dalam proses keterbukaan informasi public. Hasil penelitian menunjukan Biro Humas tidak memenuhi peran sebagai expert Prescriber dalam kegiatan yang dilakukannya. Sementara itu peran problem solving process facilitator tidak ada terlihat pada Biro Humas, hal ini dikarenakan Biro Humas belum menjalankan kegiatan verifikasi dan inventarisasi informasi untuk didiskusikan oleh pimpinan tingkat atas. Saran penelitian ini Biro Humas Provinsi Kalimantan Selatan dapat memanfaatkan sumber daya manusia yang sudah ada untuk memiliki kemampuan menjalankan tugas sebagai Humas pemerintah maupun PPID utama di Provinsi Kalsel, mengingat tidak meratanya koordinasi antar bagian pada Biro Humas. selanjutnya Biro Humas harus segera mungkin merencanakan program kegiatan beserta strategi-strategi yang berkesinambungan untuk percepatan keterbukaan informasi publik. Kata Kunci: Humas, Pemerintah, Expert Prescriber, Problem Solving Process Facilitator